Sustainable Development of Shared Mobility in China in Relation to the Privacy Paradox of Users - Yuqin Li; Hanying Guo (Journal of Advanced Transportation)
Shared mobility is an important part of a smart city transportation system. However, during the short period it has been in effect, privacy leakages have frequently occurred, and as travellers are increasingly paying attention to their privacy, leakages hinder the rapid development of shared mobility. Therefore, it is important to explore the origin of the privacy paradox in the context of shared mobility and propose some targeted measures for improvement. The privacy paradox has been attested in numerous studies, where, despite their obvious concern that their privacy will be compromised, users continued to adopt services that may compromise it. This study constructs a model for the privacy paradox based on the theory of planned behaviour, privacy calculus theory, and construal level theory. A questionnaire survey was conducted with 301 Chinese college students to quantitatively analyse the relationship between the main factors of users’ privacy paradox in the context of shared mobility. The study results showed that (a) the privacy paradox does exist in shared mobility among college students; (b) both perceived benefit and trust have a significant positive effect on near future disclosure intention, with trust being the prime motivator; (c) both privacy concern and perceived risk have significant negative effects on distant future disclosure intention, with privacy concern being the key ingredient; and (d) both near and distant future disclosure intentions have positive effects on privacy disclosure behaviour, with near future disclosure intention having a more significant influence. Further, to promote the healthy and sustainable development of China’s shared mobility industry, countermeasures and suggestions have been proposed for users, ride-sharing enterprises, and the government according to the research results.